(untitled) (The Research of Medical Science Review, 2025)
Non-Iodinated contrast media are commonly used for diagnostic and therapeutic applications. More than 1.2 million cardiac catheterizations are performed worldwide each year. Contrast Induced Nephropathy (CIN) is a serious consequence of several radiographic procedures that expose patients to contrast media. Objective: To evaluate the frequency of Contrast Induced Nephropathy in patients undergoing cardiac catheterization procedures. Design: Observational Study Place and Duration of Study: This observational study was carried out in the department of Nephrology in collaboration with the Department of Cardiology, Liaquat University Hospital, Hyderabad (October, 2023 to April, 2024). Methods: A total of 100 patients of either gender of aged between 20 to 70 years with stable ischemic heart disease undergoing cardiac catheterization were included. Patients with chronic kidney disease, renal congenital abnormalities, single kidney either congenitally or having previous nephrectomy, candidates of renal transplant or on dialysis patients were excluded. Contrast Induced Nephropathy (CIN) was defined as a relative 25% increase in serum creatinine from baseline or a 0.5 mg/dl (44μmol/l) increase in the absolute value within 72 hours of contrast administration. Statistical analysis was performed using SPSS version 26. Mean + SD was calculated for quantitative data, whereas qualitative data was illustrated in the form of frequencies and percentages. Chi-square/fisher exact test was applied to know the factors associated with CIN. P-value < 0.05 was considered as significant. Results: Mean age of the patients was 57.20 + 9.91 years and 53% were men. Obesity, hypertension, diabetes and smoking were present in 10 (10%), 53 (53%), 40 (40%) and 9 (9%) respectively. The frequency of CIN was 16 (16%) within 72 hours of post procedure. Conclusion: Patients having cardiac catheterization procedures (Angiography and PCI) have 16% occurrence of CIN, which is linked to heart failure and obesity. To lessen the clinical burden of CIN after primary PCI, early risk assessment and proactive preventive measures are necessary in clinical practice.